PERANCANGAN KAPAL GENERAL CARGO 9500 DWT KECEPATAN 13 KNOT DENGAN RUTE PELAYARAN PANJANG (LAMPUNG) - SOEKARNO HATTA (MAKASSAR) - Maria Yashinta Noviastuti, (2020)
For the sake of realizing Indonesia to become a global maritime axis, facilities that support this potential are also needed. As data obtained Indonesia has 14,572 islands and has an area of 6,292,156.82 km2. Indonesia has a huge potential in the field of sea transportation, where sea transportation services are not an important business in the distribution of goods for inter-island trade needs. The role to build Indonesia into a global maritime axis can be done by increasing the Indonesian naval fleet. By increasing the number of Indonesian naval fleets, Indonesia's growth can also increase equally in various regions. The need for ship cargo for shipping in Indonesia is also a benchmark for the design of this general cargo ship. General cargo ships are ships that carry a variety of cargo consisting of goods transported which are usually packaged goods, such as medicine, food, furniture, machinery, motorcycles and military vehicles, footwear, garments, and other goods. neatly packaged and sealed goods. The general cargo ship is equipped with a cargo crane to facilitate loading and unloading of cargo. In this study the design of the aircraft carrier was made using a regression method based on data from 2 comparative vessels. then do the lines plan, general arrangement, hydrostatic analysis, confirm analysis in accordance with IMO standards. The principal size of the ship are Loa 117.22 m long, Lpp 109.245 m, the width of the ship 16.86 m, the ladder height 7.94 m, and the height of the ship 9.5 m, with a speed of 13 knots.